1980
DOI: 10.1037/h0077721
|View full text |Cite
|
Sign up to set email alerts
|

Positive and reverse placebo effects as a function of differences in cues used in self-perception.

Abstract: Both positive and reverse placebo effects have been observed frequently but not consistently in the past. Based on a self-perception analysis of placebo responses, it was predicted that positive placebo effects would occur in individuals whose self-perceptions tended to be based on situational rather than self-produced information, whereas reverse placebo effects would be expected in subjects more responsive to self-produced cues. Subjects were designated self-produced cue responders if their reports of emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 39 publications
1
40
1
Order By: Relevance
“…In one study, this led to a "reverse" placebo effect (Duncan & Laird, 1980), and in another to a negative impact on self-esteem because of comparison with a positive stan-dard (Wilcox & Laird, 2000). Specifically, we expected that in the Unreminded condition, women who were responsive to Personal Cues and were in their premenstrual week, would report more negative feelings and less positive feelings than women not in their premenstrual week, whereas women who were unresponsive to Personal Cues would not differ as a function of where they were in their menstrual cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, this led to a "reverse" placebo effect (Duncan & Laird, 1980), and in another to a negative impact on self-esteem because of comparison with a positive stan-dard (Wilcox & Laird, 2000). Specifically, we expected that in the Unreminded condition, women who were responsive to Personal Cues and were in their premenstrual week, would report more negative feelings and less positive feelings than women not in their premenstrual week, whereas women who were unresponsive to Personal Cues would not differ as a function of where they were in their menstrual cycle.…”
Section: Resultsmentioning
confidence: 99%
“…For example, people who are induced to adopt facial expressions or postures of various emotions feel the corresponding emotions (Duclos et al, 1989), and people feel romantic attraction if they exchange mutual gazes (Kellerman, Lewis, & Laird, 1989;Williams & Kleinke, 1993). A lesser but still substantial number of studies has shown that preventing emotional behavior reduces the intensity of emotional experience (e.g., Duncan & Laird, 1980;Hazaleus & Deffenbacher, 1986;Laird et al, 1994). For example, increases in arousal lead to increased intensity of experiences of fear, anger, and passionate love (see Laird & Bresler, 1992;& Foster, Witcher, Campbell, & Green, 1998, for reviews).…”
Section: Self-perception Theorymentioning
confidence: 99%
“…Researchers thus studied potential moderating variables. This subsequent work revealed that reverse placebo effects are likely to occur on secondary assessment measures (i.e., measures of participants' belief about their underlying condition), when the expected internal state is parallel to one's actual state, and when individuals are closely examining their internal feeling state and the cause of those feelings (J. W. Duncan & Laird, 1980;Girodo, 1973;Ross & Olson, 1981). On the basis of the present studies, we believe that in addition to moderating traditional placebo effects, nonconscious goals moderate reverse placebo effects.…”
Section: Placebo Effect Researchmentioning
confidence: 99%
“…The manual also contained sample pictures of a young man's face, taken from the PoFA, displaying each of the facial expressions in a prototypical way (neutrality, WF2-5;happiness, WF2-12;sadness, WF3-28;disgust, WF3-11;surprise, WF2-16;fear, WF3-16;anger, WF3-4;Ekman & Friesen, 1976). Even though evidence suggests that facial expression of an emotion triggers experience of the emotion (Coan, Allen, & Harmon-Jones, 2001;Duncan & Laird, 1980;Strack, Martin, & Stepper, 1988), the face models were told that the aim was not necessarily to actually experience the emotion but, rather, to optimally show it on the face so that other persons could recognize it. They were instructed to display each facial expression as intensively as possible, but in a natural-looking way.…”
Section: P Smentioning
confidence: 99%